SUBSIDED FERTILIZER DISTRIBUTION IN SIDRAP DISTRICT - Achmad Amiruddin; Ihramsyah Ihramsyah; Imam Mujahidin Fahmid; Ahmad Imam Muslim (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Subsidized fertilizers have an important and strategic role in increasing agricultural productivity, but there are problems in their distribution that make farmers feel the scarcity of fertilizers. This study aims to evaluate the effectiveness of the distribution of subsidized fertilizers and determine the efficiency of the distribution of subsidized fertilizers in Sidrap District. Data collection was carried out by interviewing 12 farmers from 6 retailers and 3 distributors using accidental sampling technique. To identify the formulation of the problem, a quantitative descriptive analysis method was used with the percentage of farmers using subsidized fertilizer in accordance with the principles of the right type, amount, price, place, time, quality and to measure the efficiency of distribution can be tested using the marketing margin value. The results of the study showed that the distribution of fertilizers in Sidrap Regency as a whole was effective and efficient. Problems in the distribution of fertilizers in Sidrap Regency include the slowness of farmers in placing orders for fertilizers so that retailers need some time to restock fertilizer according to the needs of farmers, retailers sell fertilizers to other than farmer groups while farmers buy fertilizers not through farmer groups, farmers object to fees to groups farmers so that farmers buy fertilizer directly from retailers. Authors suggested to improve the fertilizer requirements database, socialize the official flow of subsidized fertilizer distribution for retailers and farmers, structure the location or scale of the retailer's business, and set a lower and upper limit for fertilizer distribution transportation costs.